Alcohol intake and risk of erectile dysfunction: a dose–response meta-analysis of observational studies. Issue 6 (November 2018) - Wang, Xiao-Ming; Bai, Yun-Jin; Yang, Yu-Bo; Li, Jin-Hong; Tang, Yin; Han, Ping
Abstract The purpose of the present study was to conduct a meta-analysis of cross-sectional studies assessing the relationship between alcohol consumption and the risk of erectile dysfunction (ED). To identify relevant studies, databases such as Pubmed, Medline, Embase, and the Cochrane Library were searched from the inception of the present study to March 2016. Finally, 24 studies (154, 295 patients) were included. We combined a study-specific odds ratio (OR) estimated by using a random effects meta-analysis. The results of our meta-analysis indicated that light to moderate alcohol consumption (<21 drinks/week) was correlated with a decreased risk of erectile dysfunction (OR = 0.71; 95% CI: 0.59–0.86;P  = 0.000). However, regular (ever vs. never) and high alcohol consumption (>21 drinks/week) had no significant influence on the prevalence of ED (regular: OR = 0.87; 95% CI: 0.75–1.07;P  = 0.062; high: OR = 0.99; 95% CI: 0.80–1.22;P  = 0.893). In a dose–response meta-analysis, a non-linear relationship was observed between alcohol consumption and risk of ED (P for non-linearity = 0.0000). In conclusion, moderate intake of alcohol exhibited a beneficial effect on the risk of ED, whereas regular and high consumption did not.